Integrating Musi River as Local Wisdom with the SETS Approach: Evaluating the Effectiveness of a Physics E-Module on High School Student Test Performance - Linda Lia; Lefudin Lefudin; Patricia Hotma Minar Lubis (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
The integration of local wisdom with the approach of science, environment, technology and society (SETS) in the development of e-modules of physics presents significant progression in educational methodologies. The research was conducted on students of SMAN 16 Palembang class XI.The instruments used in the research are documentation, walkthroughs, questionnaires and tests. The research results were obtained based on an expert review that the e-module developed was declared very valid with an average of 4.34 in terms of material, media and language aspects. At the One-to-One stage, an average of 4.17 was obtained in the practical category. At the Small Group stage, an average of 3.81 was obtained in the practical category. In the Field Test phase, it has an n-gain score of 0.72 which is in the high category and a percentage of 71.96% in the quite effective category. In conclusion, to evaluate the effectiveness of an e-modules of physics that integrates local wisdom and setting sets clarifies a promising methodology for contemporary education. The intersection of local wisdom and scientific education thus portrays a convincing view for future pedagogical approaches in high schools, defending the learning that is significant and impactful.